ECOLOGICALLY SAFE METHOD OF OBTAINING CELLULOSE FROM FLAX - Mamatvaliev Ibrohimjon Tolib oʻgʻli, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
The article presents the results of an environmentally safe method of obtaining cellulose, a raw material for the light industry of our Republic, from flax. The main factors affecting the quality indicators of the product are studied, and their optimal concentrations are found. В статье представлены результаты экологически безопасного способа получения целлюлозы из растения льна для легкой промышленности нашей Республики. Изучены основные факторы, влияющие на качественные показатели продукта, и найдены их оптимальные концентрации.